Evaluation of a surgical service in the chronic phase of a refugee camp: an example from the Thai-Myanmar border - Weerasuriya, C; Tan, S; Alexakis, L; Set, A; Rijken, M; Martyn, P; Nosten, F; McGready, R (BioMed Central, 2012)
Published literature on surgical care in refugees tends to focus on the acute ('emergent') phase of crisis situations. Here we posit that there is a substantial burden of non-acute morbidity amenable to surgical intervention among refugees in the 'chronic' phase of crisis situations. We describe surgery for non-acute conditions undertaken at Mae La Refugee Camp, Thailand over a two year period.Surgery was performed by a general surgeon in a dedicated room of Mae La Refugee Camp over May 2005 to April 2007 with minimal instruments and staff. We obtained the equivalent costs for these procedures if they were done at the local Thai District General Hospital. We also acquired the list (and costs) of acute surgical referrals to the District General Hospital over September 2006 to December 2007.855 operations were performed on 847 patients in Mae La Refugee Camp (60.1% sterilizations, 13.3% 'general surgery', 5.6% 'gynaecological surgery', 17.4% 'mass excisions', 3.5% 'other'). These procedures were worth 2,207,500 THB (75,683.33 USD) at costs quoted by the District General Hospital. Total cost encountered for these operations (including staff costs, consumables, anaesthesia and capital costs such as construction) equaled 1,280,000 THB (42,666 USD). Pertaining to acute surgical referrals to District General hospital: we estimate that 356,411.96 THB (11,880.40 USD) worth of operations over 14 months were potentially preventable if these cases had been operated at an earlier, non-acute state in Mae La Refugee Camp.A considerable burden of non-acute surgical morbidity exists in 'chronic' refugee situations. An in-house general surgical service is found to be cost-effective in relieving some of this burden and should be considered by policy makers as a viable intervention.